Preparation method of composite material, composite material and electronic equipment
By forming an oxide layer on the surface of the titanium alloy base material and sputtering in a high vacuum environment, the problems of low hardness and poor wear resistance of the oxide layer of the titanium alloy material are solved, and the wear resistance and gloss of the composite material are improved.
Patent Information
- Application Number
- CN202411545731.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-25
AI Technical Summary
The oxide layer of the existing titanium alloy materials has small hardness and poor wear resistance, which is easy to be damaged during use.
By forming an oxide layer on the surface of the titanium alloy substrate and sputtering in a high vacuum environment, a ceramic layer is formed to enhance the wear resistance and light transmittance of the oxide layer.
It improves the wear resistance and gloss of the composite material, ensures a good appearance and extends service life.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and more specifically, to a method for preparing a composite material, a composite material and an electronic device. Background Art
[0002] In the related art, electronic devices usually include metal housings. For example, the metal housing is made of titanium alloy material. The surface of the titanium alloy material can form an oxide layer of different colors on the surface by anodizing. However, the oxide layer has a low hardness and poor wear resistance, and is easily damaged during use.
[0003] Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention
[0004] One object of the present invention is to provide a new technical solution for a method for preparing a composite material.
[0005] According to a first aspect of the present invention, a method for preparing a composite material is provided. The method comprises:
[0006] Providing a titanium alloy substrate, and forming an oxide layer on the surface of the titanium alloy substrate;
[0007] The titanium alloy substrate is placed in a cavity of a sputtering device, wherein the target material of the sputtering device is a semiconductor or a metal, and the vacuum degree of the cavity is greater than or equal to 10 -3 Pa;
[0008] Filling the cavity with argon gas and applying a bias voltage to perform glow cleaning on the surface of the titanium alloy substrate;
[0009] Oxygen gas is filled into the cavity for sputtering to form a ceramic layer on the surface of the oxide layer, wherein the oxygen-argon ratio in the cavity is 1:1-1:4 and the sputtering gas pressure is 0.2Pa-0.8Pa.
[0010] Optionally, the thickness of the ceramic layer is 20nm-80nm.
[0011] Optionally, during sputtering, the temperature in the chamber is 150°C-200°C.
[0012] Optionally, the target material is made of at least one of silicon, aluminum, and zirconium.
[0013] Document classification: ConfidentialDocument classification: Confidential
[0014] Optionally, the refractive index of the ceramic layer is 1.4-1.6, the light transmittance of the ceramic layer is 89%-96%, and the color difference value ΔE of the ceramic layer is ≤2.
[0015] Optionally, during sputtering, the bias voltage of the sputtering device is 600V-1200V.
[0016] Optionally, the ceramic layer is amorphous ceramic.
[0017] According to a second aspect of the present invention, a composite material is provided. The composite material is prepared according to the composite material preparation method of the present invention.
[0018] Optionally, the composite material includes a titanium alloy substrate, an oxide layer and a ceramic layer, wherein the oxide layer is formed on a surface of the titanium alloy substrate, and the ceramic layer covers the oxide layer.
[0019] According to a third aspect of the present invention, an electronic device is provided, comprising the composite material of the present invention.
[0020] In an embodiment of the present invention, the preparation method of the composite material is to control the vacuum degree of the cavity to be higher than or equal to 10 -3 Pa, can effectively prevent the ceramic layer from being contaminated, and improve the transmittance of the ceramic layer. The surface of the target material can be effectively cleaned by glow cleaning. By controlling the oxygen-argon ratio during sputtering to 1:1-1:4, the presence of semiconductors or metals and oxygen vacancies in the ceramic layer can be effectively avoided, and no peroxide-type oxide film will be formed, thereby making the ceramic layer have a high transmittance. In addition, by controlling the sputtering pressure to 0.2Pa-0.8Pa, the argon content in the cavity is moderate, the amount of sputtered target particles is moderate, and the deposition rate of the ceramic layer is high. The ceramic layer prepared by this preparation method can effectively protect the oxide layer, improve the wear resistance of the composite material, and the composite material has high light chromaticity and good appearance.
[0021] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0023] Figure 1 is a flow chart of a method for preparing a composite material according to an embodiment of the present invention.
[0024] Figure 2 Schematic diagram of the structure of a composite material according to an embodiment of the present invention.
[0025] Description of reference numerals:
[0026] 10. Ceramic layer; 20. Oxide layer; 30. Titanium alloy substrate.
[0027] Document classification: ConfidentialDocument classification: Confidential DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0029] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0030] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.
[0031] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0032] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0033] According to one embodiment of the present invention, a method for preparing a composite material is provided. Figure 1-Figure 2 As shown, the preparation method comprises:
[0034] Providing a titanium alloy substrate 30, and forming an oxide layer 20 on the surface of the titanium alloy substrate 30;
[0035] The titanium alloy substrate 30 is placed in a cavity of a sputtering device, the target material of the sputtering device is metal, and the vacuum degree of the cavity is greater than or equal to 10 -3 Pa;
[0036] Filling the cavity with argon gas and applying a bias voltage to perform glow cleaning on the target material;
[0037] Oxygen gas is filled into the cavity to perform a sputtering reaction to form a ceramic layer 10 on the surface of the oxide layer 20 , wherein the oxygen-argon ratio in the cavity is 1:4-1:1, and the sputtering gas pressure is 0.2Pa-0.8Pa.
[0038] Specifically, the preparation method uses physical vapor deposition to form a ceramic layer 10 on the surface of the oxide layer 20. The titanium alloy substrate 30 is an alloy made of titanium metal and other metals (for example, at least one of molybdenum, vanadium, chromium, manganese, iron, cobalt, nickel, copper, etc.). The surface of the titanium alloy substrate 30 forms an oxide layer 20 by an oxidation process. The oxide layer 20 can reflect or interfere with the incident light, thereby presenting a color. Depending on the thickness of the oxide layer 20, the oxide layer 20 can present different colors, such as yellow, purple, blue, light blue, silver, pink, cobalt blue, green, etc. Optionally, an anodizing process is used to form an oxide layer 20 on the surface of the titanium alloy substrate 30. The thickness of the oxide layer 20 is controlled by controlling the current, time, voltage, etc. of the anodizing so that the oxide layer 20 presents different colors. Of course, the oxidation process is not limited to anodizing, and those skilled in the art can choose according to actual needs.
[0039] The titanium alloy substrate 30 is placed in the cavity of the sputtering equipment. The sputtering equipment includes a vacuum system, a vacuum chamber and a sputtering system. The vacuum system is connected to the vacuum chamber. There is a cavity in the vacuum chamber. The vacuum system is used to evacuate the cavity to form a set vacuum degree. The sputtering system includes a power supply, a target material and a magnetic field generating device. The target material is connected to the power supply, the target material serves as a cathode, and the wall of the vacuum chamber serves as an anode. The magnetic field generating device is used to form a magnetic field in the cavity. During operation, argon gas is introduced into the cavity. Under the action of the electric field, the argon gas is ionized to form argon ions, the electrons are accelerated by the electric field and bound around the target material by the magnetic field, and the argon ions bombard the target material under the action of the electric field, thereby sputtering target material particles, such as target material atoms or target material molecules, and the target material particles are oxidized under the action of oxygen to form oxides, and the oxides are deposited on the surface of the oxide layer 20 to form a ceramic layer 10.
[0040] The target material is a semiconductor or a metal. Optionally, the semiconductor is, for example, Si, Ge, etc., and the metal is, for example, Al, Zr, etc. The vacuum degree of the chamber is greater than or equal to 10 -3 Pa refers to the air pressure in the cavity less than or equal to 10 -3 The lower the vacuum degree, the higher the concentration of gas molecules in the cavity. The gas molecules will collide with the sputtered target particles, causing the ceramic layer 10 to be contaminated. In the embodiment of the present invention, the vacuum degree of the cavity is greater than or equal to 10 -3 Pa, so that the concentration of gas molecules in the cavity is low and the ceramic layer 10 is not easily contaminated.
[0041] Before sputtering, it is necessary to ensure that the surface of the target material is clean and free of dirt. In an embodiment of the present invention, the target material is cleaned by glow cleaning. During cleaning, the titanium alloy substrate 30 is placed in the chamber, and no oxygen is introduced into the chamber. Glow cleaning converts argon gas into a plasma state through high-voltage discharge, forming a plasma glow discharge phenomenon. During the glow discharge process, argon ions are accelerated under the action of the electric field to bombard the target material, thereby achieving the effect of cleaning the surface of the target material.
[0042] When sputtering is performed, oxygen and argon need to be continuously filled into the chamber. Argon is used to bombard the target material. The sputtered target particles react with oxygen to undergo an oxidation reaction to form oxides. The oxides are deposited on the surface of the oxide layer 20 to form a ceramic layer 10. In an embodiment of the present invention, the oxygen-argon ratio is the ratio of the flow rates of oxygen and argon into the chamber. When the oxygen-argon ratio is less than 1:4, the sputtered target particles are prone to insufficient oxidation, which causes the ceramic layer 10 to have target elements and a large number of oxygen vacancies. As a result, the ceramic layer 10 absorbs the incident light more, which reduces the transmittance of the ceramic layer 10, and the surface particles of the oxide layer 20 are coarse and the oxide layer 20 is loose. When the oxygen-argon ratio is greater than 1:1, the excessive oxygen in the cavity reacts with the target particles to form an oxide film layer on the surface of the oxide layer 20, which reduces the sputtering rate and causes an over-oxygen ceramic oxide film layer to appear in the ceramic layer 10, resulting in a decrease in the transmittance of the ceramic layer 10. When the oxygen-argon ratio is 1:4-1:1, the presence of semiconductors or metals and oxygen vacancies in the ceramic layer 10 can be effectively avoided, and no peroxide-type oxide film is formed, thereby making the ceramic layer 10 have high light transmittance.
[0043] The sputtering pressure mainly affects the sputtering plastic. When the sputtering pressure is less than 0.2Pa, the sputtering pressure is too low, the argon content is small, the sputtered target particles are small, and the deposition rate of the ceramic layer 10 is low. When the sputtering pressure is greater than 0.8Pa, the argon content is too high, the sputtered target particles are large, and the sputtered target particles collide frequently with gas molecules (such as argon and oxygen), which reduces the energy of the target particles and makes the deposition rate of the ceramic layer 10 low. When the sputtering pressure is 0.2Pa-0.8Pa, the argon content is moderate, the amount of sputtered target particles is moderate, and the deposition rate of the ceramic layer 10 is high.
[0044] In an embodiment of the present invention, the preparation method of the composite material is to control the vacuum degree of the cavity to be higher than or equal to 10 -3Pa, can effectively prevent the ceramic layer 10 from being contaminated, and improve the transmittance of the ceramic layer 10. The surface of the target material can be effectively cleaned by glow cleaning. By controlling the oxygen-argon ratio during sputtering to 1:1-1:4, the presence of semiconductors or metals and oxygen vacancies in the ceramic layer 10 can be effectively avoided, and no peroxide-type oxide film will be formed, thereby making the transmittance of the ceramic layer 10 high. In addition, by controlling the sputtering gas pressure to 0.2Pa-0.8Pa, the argon content in the cavity is moderate, the amount of sputtered target particles is moderate, and the deposition rate of the ceramic layer 10 is high. The ceramic layer 10 prepared by this preparation method can effectively protect the oxide layer 20, improve the wear resistance of the composite material, and the composite material has high light chromaticity and good appearance.
[0045] In a specific embodiment of the present invention, the thickness of the ceramic layer 10 is 20nm-80nm.
[0046] The thickness of the ceramic layer 10 has a significant effect on the strength and wear resistance of the ceramic layer 10. In this embodiment, the thickness of the ceramic layer 10 is controlled within the range of 20nm-80nm by controlling parameters such as the magnetron sputtering time and the oxygen-argon ratio. When the thickness of the ceramic layer 10 is too small, the strength of the ceramic layer 10 is small and the wear resistance is poor; when the thickness of the ceramic layer 10 is too large, the light transmittance of the ceramic layer 10 is low, resulting in a poor appearance of the composite material. When the thickness of the ceramic layer 10 is 20nm-80nm, the ceramic layer 10 can have both high strength and wear resistance and high light transmittance, and the composite material has a good appearance.
[0047] Optionally, the thickness of the ceramic layer 10 is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, etc. The above values make the ceramic layer 10 have high strength and wear resistance, high light transmittance, and good appearance of the composite material.
[0048] Of course, the thickness of the ceramic layer 10 is not limited to the above embodiment, and those skilled in the art can set it according to actual needs.
[0049] In a specific embodiment of the present invention, during sputtering, the temperature in the chamber is 150° C.-200° C.
[0050] In this embodiment, the vacuum chamber is provided with a heating device, and the vacuum chamber is heated by the heating device so that the temperature in the cavity is 150°C-200°C. It should be noted that if the temperature of the chamber is too high, it will cause the phase change of the target material, affect the quality of the ceramic layer 10 and easily generate thermal stress, which will cause internal defects or cracks in the ceramic layer 10; if the chamber temperature is too low, it will cause insufficient reaction between the sputtered particles and oxygen, oxygen vacancies will exist in the ceramic layer 10, and the ceramic layer 10 will have many defects. When the temperature in the cavity is 150°C-200°C, the phase change of the target material and the thermal stress of the ceramic layer 10 can be effectively avoided, and there are fewer defects in the ceramic layer 10.
[0051] Optionally, the temperature in the cavity is 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., etc. The above values can effectively avoid phase change of the target material and thermal stress of the ceramic layer 10 , and there are few defects in the ceramic layer 10 .
[0052] Of course, the temperature of the cavity is not limited to the above embodiments, and those skilled in the art can set it according to actual needs.
[0053] In a specific embodiment of the present invention, the target material is made of at least one of silicon, aluminum and zirconium.
[0054] In this embodiment, when the target material is silicon, the main component of the ceramic layer 10 is silicon dioxide. When the target material is aluminum, the main component of the ceramic layer 10 is aluminum oxide. When the target material is zirconium, the main component of the ceramic layer 10 is zirconium oxide. The above ceramic layers 10 have high hardness, wear resistance, and high light transmittance.
[0055] Of course, the material of the target is not limited to the above embodiments, and those skilled in the art can set it according to actual needs.
[0056] In a specific embodiment of the present invention, the refractive index of the ceramic layer 10 is 1.4-1.6.
[0057] Document classification: ConfidentialDocument classification: ConfidentialThe light transmittance of the ceramic layer 10 is 89%-96%, and the color difference value △E≤2 of the ceramic layer 10.
[0058] The refractive index, transmittance, color difference value, etc. of the ceramic layer 10 affect the appearance of the composite material. By controlling the material, thickness, etc. of the ceramic layer 10, the refractive index, transmittance and color difference value of the ceramic layer 10 can be controlled. A refractive index that is too small is likely to result in a low glossiness of the ceramic layer 10; conversely, a refractive index that is too large is likely to result in color deviation of the ceramic layer 10. When the refractive index of the ceramic layer 10 is 1.4-1.6, the glossiness of the ceramic layer 10 can be high and the color deviation of the ceramic layer 10 can be avoided. If the transmittance of the ceramic layer 10 is too small, the color glossiness of the oxide layer 20 can be reduced; conversely, if the transmittance of the ceramic layer 10 is too large, the thickness of the ceramic layer 10 needs to be thinned, which affects the strength of the ceramic layer 10. When the transmittance of the ceramic layer 10 is 89%-96%, the color glossiness of the oxide layer 20 can be ensured to be high and the thickness of the ceramic layer 10 can be avoided to be small. The color difference value △E represents the degree of difference between the two colors. The larger the color difference value △E, the greater the difference between the two colors, and the smaller the color difference value △E, the smaller the difference between the two colors. If the color difference value of the ceramic layer 10 is too large, the color of the oxide layer 20 will deviate, resulting in a poor appearance of the composite material. When the color difference value △E of the ceramic layer 10 is ≤2, the color deviation of the oxide layer 20 can be effectively avoided, and the appearance of the composite material is good.
[0059] Optionally, the refractive index of the ceramic layer 10 is 1.4, 1.45, 1.5, 1.55, 1.6, etc. The light transmittance of the ceramic layer 10 is 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, etc. The color difference value ΔE of the ceramic layer 10 is 0.5, 1, 1.5, 2, etc.
[0060] Of course, the refractive index, transmittance, color difference value, etc. of the ceramic layer 10 are not limited to the above embodiments, and those skilled in the art can make selections according to actual needs.
[0061] In a specific embodiment of the present invention, during sputtering, the bias voltage of the sputtering device is 600V-1200V.
[0062] During sputtering, the voltage of the power supply is controlled by the control system so that the bias voltage of the sputtering device is maintained between 600V and 1200V. A bias voltage that is too high can easily cause gas breakdown in the cavity, making the surface of the ceramic layer 10 loose and causing pores; conversely, a bias voltage that is too low can cause the energy of the sputtered particles to be low, and the structure of the ceramic layer 10 to be loose and have low strength. When the bias voltage of the sputtering device is 600V-1200V, it can avoid both the gas breakdown phenomenon in the cavity and the low energy of the sputtered particles, and the structure of the ceramic layer 10 is dense and has high strength. Optionally, the bias voltage of the sputtering device is 600V, 700V, 800V, 900V, 1000V, 1100V, 1200V, etc. The above values can avoid both the gas breakdown phenomenon in the cavity and the low energy of the sputtered particles, and the structure of the ceramic layer 10 is dense and has high strength.
[0063] Document classification: ConfidentialDocument classification: Confidential
[0064] Of course, the bias voltage of the sputtering device is not limited to the above embodiments, and those skilled in the art can select it according to actual needs.
[0065] In a specific embodiment of the present invention, the ceramic layer 10 is amorphous ceramic.
[0066] The ceramic layer 10 of the embodiment of the present invention is an amorphous ceramic. The arrangement of atoms or ions inside the amorphous ceramic does not have a regular crystal structure, showing a state of short-range order and long-range disorder. Compared with crystalline ceramics, the microstructure of amorphous ceramics does not have obvious lattice boundaries. Amorphous ceramics have the characteristics of high strength, high toughness and good wear resistance.
[0067] According to a second embodiment of the present invention, a composite material is provided, which is prepared according to the composite material preparation method of the present invention.
[0068] The composite material of the present invention at least includes all the beneficial effects of the above embodiments, which will not be described in detail here.
[0069] In a specific embodiment of the present invention, Figure 2 As shown, the composite material includes a titanium alloy substrate 30 , an oxide layer 20 and a ceramic layer 10 . The oxide layer 20 is formed on the surface of the titanium alloy substrate 30 , and the ceramic layer 10 covers the oxide layer 20 .
[0070] The composite material has the characteristics of light weight, glossy surface, good appearance, good wear resistance and long service life.
[0071] According to a third embodiment of the present invention, an electronic device is provided, which includes the composite material of the present invention.
[0072] The electronic device may be a mobile phone, a smart watch, a computer, a VR device, an AR device, a speaker, etc. The composite material is used as a housing of the electronic device.
[0073] The electronic device of the present invention also includes at least all the beneficial effects of the above embodiments, which will not be elaborated here.
[0074] The following describes in detail the preparation method of the composite material of the present invention with specific examples and comparative examples. It is worth noting that the following description is only exemplary and not a specific limitation of the present invention.
[0075] Example 1
[0076] In this embodiment, the method for preparing the composite material includes:
[0077] (1) An anodic oxidation process is used to form an oxide layer 20 on the surface of the titanium alloy substrate 30.
[0078] (2) The titanium alloy substrate 30 is placed in the cavity of the sputtering device. The target material of the sputtering device is Si, and the vacuum degree of the cavity is 10 -3 Pa.
[0079] Document classification: ConfidentialDocument classification: Confidential
[0080] (3) When the vacuum degree reaches 10 -3 When the pressure is 0.045V, argon gas is introduced into the cavity, and the partial pressure of argon gas is 0.2 Pa. The bias voltage is 800 V, and the temperature in the cavity is 180° C. The glow cleaning time is 5 minutes.
[0081] (4) After the glow cleaning is completed, oxygen is introduced into the cavity to control the oxygen-argon ratio to be 1:1. The sputtering pressure is 0.3 Pa. The sputtering time is 20 minutes. The thickness of the ceramic layer 10 of the composite material finally obtained is 20 nm.
[0082] Example 2
[0083] In this embodiment, the method for preparing the composite material includes:
[0084] (1) An anodic oxidation process is used to form an oxide layer 20 on the surface of the titanium alloy substrate 30.
[0085] (2) The titanium alloy substrate 30 is placed in the cavity of the sputtering device. The target material of the sputtering device is Si, and the vacuum degree of the cavity is 10 -3 Pa.
[0086] (3) When the vacuum degree reaches 10 -3 When the pressure is 0.045V, argon gas is introduced into the cavity, and the partial pressure of argon gas is 0.2 Pa. The bias voltage is 800 V, and the temperature in the cavity is 180° C. The glow cleaning time is 5 minutes.
[0087] (4) After the glow cleaning is completed, oxygen is introduced into the cavity to control the oxygen-argon ratio to be 1:1. The sputtering pressure is 0.3 Pa. The sputtering time is 40 minutes. The thickness of the ceramic layer 10 of the composite material finally obtained is 50 nm.
[0088] Comparative Example
[0089] In this embodiment, the method for preparing the composite material includes:
[0090] (1) An anodic oxidation process is used to form an oxide layer 20 on the surface of the titanium alloy substrate 30.
[0091] (2) The titanium alloy substrate 30 is placed in the cavity of the sputtering device. The target material of the sputtering device is Si, and the vacuum degree of the cavity is 10 -3 Pa.
[0092] (3) When the vacuum degree reaches 10 -3 When the pressure is 0.045V, argon gas is introduced into the cavity, and the partial pressure of argon gas is 0.2 Pa. The bias voltage is 800 V, and the temperature in the cavity is 180° C. The glow cleaning time is 5 minutes.
[0093] (4) After the glow cleaning is completed, oxygen is introduced into the cavity to control the oxygen-argon ratio to be 1:5. The sputtering pressure is 0.9 Pa. The sputtering time is 80 minutes. The thickness of the ceramic layer 10 of the composite material finally obtained is 110 nm.
[0094] Performance Testing:
[0095] The refractive index, light transmittance, and color difference ΔE of the composite materials prepared by the preparation methods of Example 1, Example 2, and the comparative example were measured respectively, and the composite materials were subjected to a 4h vibration wear resistance test and the color effect of the composite materials was judged by observation. The final results are shown in Table 1.
[0096] Table 1 - Performance comparison of the composite materials of Example 1, Example 2 and Comparative Example
[0097] Refractive Index △E Light transmittance 4h vibration wear resistance Color Effects Example 1 1.4 1.2 96% OK OK Example 2 1.6 1.5 90% OK OK Comparative Example 1.9 20 80% OK NG
[0098] As can be seen from Table 1, Example 1 and Example 2 are prepared by the preparation method of the present invention. Since the oxygen-argon ratio in the cavity is controlled to be 1:1 and the sputtering pressure is 0.3Pa in the preparation method, a ceramic layer 10 with good performance is finally obtained. Among them, the refractive index of the ceramic layer 10 of Example 1 is 1.4, and the refractive index of the ceramic layer 10 of Example 2 is 1.6. The light transmittance of the ceramic layer 10 of Example 1 is 96%, and the light transmittance of the ceramic layer 10 of Example 2 is 90%. The color difference value △E of the ceramic layer 10 of Example 1 is 1.2, and the color difference rate of the ceramic layer 10 of Example 2 is 1.5. After 4 hours of vibration wear resistance test, the appearance of the ceramic layer 10 of Example 1 and Example 2 is good and not damaged. The composite materials of Example 1 and Example 2 are bright and shiny. However, in the preparation method of the comparative example, the oxygen-argon ratio in the cavity is 1:5, and the sputtering pressure is 0.3Pa. The ceramic layer 10 finally obtained had a refractive index of 1.9, a light transmittance of 80%, and a color difference value ΔE of 20. After a 4-hour vibration wear test, relatively severe wear occurred, and the composite material had severe color deviation.
[0099] In summary, the preparation methods of Example 1 and Example 2 control the vacuum degree of the cavity to be equal to 10 -3Pa, which can effectively prevent the ceramic layer 10 from being contaminated and improve the transmittance of the ceramic layer 10. The surface of the target material can be effectively cleaned by glow cleaning. By controlling the oxygen-argon ratio during sputtering to 1:1, the presence of semiconductors or metals and oxygen vacancies in the ceramic layer 10 can be effectively avoided, and no peroxide-type oxide film will be formed, thereby making the transmittance of the ceramic layer 10 high. In addition, by controlling the sputtering gas pressure to 0.3Pa, the argon content is moderate, the amount of sputtered target particles is moderate, and the deposition rate of the ceramic layer 10 is high. The ceramic layer 10 prepared by this preparation method can effectively protect the oxide layer 20, improve the wear resistance of the composite material, and make the composite material have high gloss and good appearance.
[0100] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.
[0101] Although some specific embodiments of the present invention have been described in detail by way of example,
[0102] Document Classification: Confidential Document Classification: Confidential Those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art should understand that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A method for preparing a composite material, characterized in that: include: Providing a titanium alloy substrate, and forming an oxide layer on the surface of the titanium alloy substrate; The titanium alloy substrate is placed in a cavity of a sputtering device, wherein the target material of the sputtering device is a semiconductor or a metal, and the vacuum degree of the cavity is greater than or equal to 10 -3 Pa; Filling the cavity with argon gas and applying a bias voltage to glow clean the surface of the sputtered target material; Oxygen gas is filled into the cavity for sputtering to form a ceramic layer on the surface of the oxide layer, wherein the oxygen-argon ratio in the cavity is 1:1-1:4 and the sputtering gas pressure is 0.2Pa-0.8Pa.
2. The preparation method according to claim 1, characterized in that: The thickness of the ceramic layer is 20nm-80nm.
3. The preparation method according to claim 1, characterized in that: During sputtering, the temperature in the chamber is 150°C-200°C.
4. The preparation method according to claim 1, characterized in that: The target material is made of at least one of silicon, aluminum and zirconium.
5. The preparation method according to claim 1, characterized in that: The refractive index of the ceramic layer is 1.4-1.6, the light transmittance of the ceramic layer is 89%-96%, and the color difference value ΔE of the ceramic layer is ≤2.
6. The preparation method according to claim 1, characterized in that: During sputtering, the bias voltage of the sputtering equipment is 600V-1200V.
7. The preparation method according to claim 1, characterized in that: The ceramic layer is amorphous ceramic.
8. A composite material, characterized in that The composite material is prepared according to the composite material preparation method according to any one of claims 1 to 7.
9. The composite material according to claim 8, characterized in that The invention comprises a titanium alloy substrate, an oxide layer and a ceramic layer. The oxide layer is formed on the surface of the titanium alloy substrate, and the ceramic layer covers the oxide layer.
10. An electronic device, characterized in that: Comprising the composite material as claimed in claim 8 or 9.